Plan Estratégico para el Desarrollo Comunitario con enfoque a la Economía Social y Solidaria de la comunidad Shuid, cantón Alausí - Lema Pilamunga, Luis Gonzalo (2023)
ABSTRACT: This research work is aimed at identifying the unmet needs of the Shuid community, an indigenous community belonging to the Guasuntos parish, Alausí canton, Chimborazo province. Through a situational diagnosis, knowledge of reality was accessed with the inhabitants of the community as the main source of information. For the situational diagnosis was constructed in a participatory manner and rural sounding tools of a mixed research (quantitative – qualitative) according to. The purpose of the study is to develop a (Hernández Sampieri, 2018, p. 641) Strategic Plan for Community Development with a focus on the Social and Solidarity Economy of the Shuid community, Alausí canton, which will become a tool for strengthening the management of the quality of life of 572 families in the community, allowing through its leaders to implement the management of the objectives set out in the proposal, through the relationship with the competent bodies such as Non-Governmental Organizations, the Parish GAD of Guasuntos, Municipal GAD of the Alausí canton, provincial GAD of Chimborazo and more State institutions within the framework of their competences. The diagnosis was made on the following factors: Housing, Health, Education, Production and Economic Situation of the family. A strategic plan shows a detailed program for change within a community, leading a community from a utopian vision to a specific plan of action, so that the development and implementation of a Strategic Plan benefits community development in the canton Alausí, and in turn the specific proposal of the Community Development Plan, through the formulation of competitive strategies, will make our corporate objectives executed according to the planning, determination of the vision and mission, the objective and prioritization of projects. KEY WORDS: Planning, Community Planning, Community Development, Social and Solidarity Economy, Governance, Sustainable Development, Empowerment